Reflex Inhibition of Renal Sympathetic Nerve Activity during Myocardial Ischemia Mediated by Left Ventricular Receptors with Vagal Afferents in Dogs - Thames, Marc D. (1979)
The major goal of this investigation was to determine if activation of cardiac receptors during coronary artery occlusion could inhibit efferent renal sympathetic nerve activity. In nine chloralose anesthetized dogs with only carotid (n = 3) or with sinoaortic (n = 6) baroreceptors operative, anterior descending coronary artery (LAD) occlusion resulted in a small decrease in mean arterial pressure (−9.8±5.1 mm Hg, NS) and in a significant (P < 0.05) increase in renal nerve activity (24.0±4.1%). In these dogs, circumflex coronary artery (Cx) occlusion resulted in greater hypotension (−18.4±4.0 mm Hg), and yet no change (1.1±9%) in renal nerve activity was noted. Changes in left atrial pressure during LAD and Cx occlusion were not different. In seven dogs with carotid sinus denervation, coronary occlusions resulted in decreases both in arterial pressure and in renal nerve activity which were consistently greater during Cx occlusion. The responses to coronary occlusion in six dogs after sinoaortic deafferentation were similar to those observed with only carotid sinuses denervated. In all experiments, vagotomy abolished the difference in the blood pressure responses and the decreases in renal sympathetic nerve activity during Cx occlusion. Vagotomy also abolished the decrease in nerve activity during LAD occlusion in dogs with carotid or sinoaortic denervation. These data show that Cx occlusion and, to a lesser degree, LAD occlusion resulted in reflex withdrawal of renal sympathetic nerve activity mediated by left ventricular receptors with vagal afferents. The reflex withdrawal of renal nerve activity during Cx occlusion occurred in spite of hypotension and the presence of functioning sinoaortic baroreceptors.